Modelling upstream fish passage in standard box culverts: Interplay between turbulence, fish kinematics, and energetics. (29th January 2018) - Wang, H.; Chanson, H.
Abstract: Box culverts are common hydraulic structures along rivers and streams, in rural and urban water systems. The expertise in fish‐friendly culvert design is limited, sometimes leading to adverse impact on the catchment ecosystem or to uneconomical structures. Basic dimensional considerations highlight a number of key parameters relevant to any laboratory modelling of upstream fish passage, including the ratio of fish speed fluctuations to fluid velocity fluctuations, the ratios of fish dimensions to turbulent length scale, and the fish species. Alternately, the equation of conservation of momentum may be applied to an individual fish, yielding some deterministic estimate of instantaneous thrust and power expended during fish swimming, including the associated energy consumption. The rate of work required by the fish to deliver thrust is proportional to the cube of the local fluid velocity, and the model results demonstrate the key role of slow‐velocity regions in which fish will minimize their energy consumption when swimming upstream.